Desempeño productivo y económico de cuatro densidades del cultivo de alevinos de Piaractus brachypomus (Cuvier, 1816) “paco” (Pisces: Serrasalmidae) en jaulas flotantes, Yurimaguas – Loreto, 2023 - Vásquez Ynga, Cristian Gilmar (2024)
This study aimed to evaluate the productive and economic performance of four stocking densities of P. brachypomus “paco” fingerlings in floating cages in Yurimaguas, Loreto. A completely randomized experimental design (CRD) was applied, establishing four treatments with stocking densities of 6, 9, 12, and 15 fingerlings/m³, with three replicates each. A population of 126 fry was used, distributed across twelve experimental units, over a period of 120 days. The results showed that the lowest stocking density (6 fingerlings/m³) yielded the best productive performance indicators, with greater growth (LG = 15.9 ± 0.3 cm, WG = 223.9 ± 27.4 g, SGR = 3.11 ± 0.04 %·day─1) and higher feed efficiency (FCR = 1.91 ± 0.03) compared to higher densities (9, 12, and 15 fingerlings/m³). In economic terms, this treatment also showed the lowest production cost (CPKg = S/ 3.33 ± 0.05), the best Benefit/Cost ratio (B/C = 2.70 ± 0.04), and the highest Profitability (R = 170.48 ± 4.29%). It revealed that, as the cultivation density increased, so did the competition for resources, negatively affecting growth. Although higher densities generated greater BeN (S/ 12.89 ± 0.31), the R and B/C ratio were optimal at the lowest density. These findings suggest that proper management of stocking density is crucial to maximizing productive and economic performance in P. brachypomus aquaculture.